In vitro Photodynamic Therapy of Polymicrobial Biofilms Commonly Associated With Otitis Media - Bair, Kirsten L.; Shafirstein, Gal; Campagnari, Anthony A. (Frontiers in Microbiology, 2020)
Otitis media (OM) is a prevalent pediatric infection characterized by painful inflammation of the middle ear. There are more than 700 million cases of OM diagnosed globally each year, with 50% of affected children under five years of age. Further, OM is the most common reason for children to receive antibiotic treatment in developed countries. The most recent work on this dynamic disease indicates that biofilms and polymicrobial infections play a role in recurrent OM and chronic OM, which are difficult to eradicate using the standard antibiotic protocol. Antimicrobial photodynamic therapy (aPDT) is a promising new strategy for the treatment of resistant bacteria and persistent biofilms which lead to chronic infections. aPDT is known for its success in oncological, dermatological, and dental applications, our work focuses on its efficacy as it relates to otopathogens responsible for OM. Previous studies from our laboratory and others have shown that M. catarrhalis is susceptible to different forms of aPDT. However, many cases of OM involve multiple bacteria and to date no one has investigated the efficacy of this technology on these complex polymicrobial biofilms. We treated polymicrobial biofilms of the three most common otopathogens Streptococcus pneumoniae, Moraxella catarrhalis and non-typeable Haemophilus influenzae with the photosensitizer Chlorin e6 (Ce6) and a continuous wave 405 ± 10 nm light emitted diode. Our preliminary data show significant bactericidal activity on polymicrobial biofilms associated with OM. These studies indicate that aPDT warrants further analysis as a treatment for OM and our results provide the foundation for future studies designed to identify the optimal aPDT parameters for polymicrobial biofilm-associated infections of the middle ear.